2019
DOI: 10.2196/12615
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid, Mobile Neurocognitive Screening Test to Aid in Identifying Cognitive Impairment and Dementia (BrainCheck): Cohort Study

Abstract: Background The US population over the age of 65 is expected to double by the year 2050. Concordantly, the incidence of dementia is projected to increase. The subclinical stage of dementia begins years before signs and symptoms appear. Early detection of cognitive impairment and/or cognitive decline may allow for interventions to slow its progression. Furthermore, early detection may allow for implementation of care plans that may affect the quality of life of those affected and their caregivers. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 27 publications
(28 reference statements)
6
44
3
Order By: Relevance
“…Many studies have previously examined neurocognitive tests and identified a few top neurocognitive classifiers using non-machine learning methods, but they are not discussed here [9,[11][12][13] (see reviews by Abd Razak In sum, our results are comparable or compared favorably with previous studies although comparisons were not made on the same datasets. Our study is novel in that we employed a nonsupervised learning (as opposed to supervised learning) method, applied to a large and multi-center ADNI dataset with commonly used measures.…”
Section: Risk Score Modelsupporting
confidence: 66%
See 1 more Smart Citation
“…Many studies have previously examined neurocognitive tests and identified a few top neurocognitive classifiers using non-machine learning methods, but they are not discussed here [9,[11][12][13] (see reviews by Abd Razak In sum, our results are comparable or compared favorably with previous studies although comparisons were not made on the same datasets. Our study is novel in that we employed a nonsupervised learning (as opposed to supervised learning) method, applied to a large and multi-center ADNI dataset with commonly used measures.…”
Section: Risk Score Modelsupporting
confidence: 66%
“…A large array of neurocognitive tests are currently used to detect cognitive impairment and classify amongst normal controls (CN), EMCI, LMCI and AD [7][8]. Many studies have identified a few top classifiers using logistic regression and machine learning methods [9][10][11][12][13][14][15][16][17][18]. Some studies have also used MRI and genetic data in conjunction with neurocognitive measures for classification [19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that some computerized cognitive tests demonstrate high accuracy in differentiating dementia patients from healthy participants, but do not have adequate psychometrics to distinguish MCI from dementia [19][20][21][22] . Ideally, computerized cognitive tests would aim to be more rapid and maximize accessibility to This study evaluated BrainCheck, a computerized cognitive test battery previously validated for its diagnostic accuracy for the detection of concussion [24] and dementia-related cognitive decline [25] . BrainCheck is portable, allows for self and remote administration, and can be reimbursed by insurance plans in the US.…”
Section: Introductionmentioning
confidence: 99%
“…p-values are adjusted with the Benjamini-Hochberg method. The BrainCheck Overall Score is a composite of all individual assessments within the BrainCheck battery, representing overall performance (See details in Method 2.4).Using an existing normative population database, partly compiled from controls in previous studies[24,25] , the Overall Score was adjusted for age and the device used to generate the normalized BrainCheck Overall Scores. The normalized BrainCheck Overall Scores differed significantly among these three groups ( p <0.05).…”
mentioning
confidence: 99%
“…BrainCheck Memory ( ) is available on any Apple device and has been modified to detect age-related cognitive decline by measuring immediate and delayed recall, Trail Making Tests A and B, Stroop Test and Digit Symbol Substitution Task. In a recent large cohort study ( 54 ) in participants aged >49 years, BrainCheck Memory was administered by research staff, with scores significantly correlating with Saint Louis University Mental Status exam scores, Mini-Mental State Examination (MMSE) scores and MoCA scores. BrainCheck Memory was able to differentiate healthy controls from cognitively impaired participants ( p =.02) and BrainCheck Memory composite scores were found to have a sensitivity of 81% and specificity of 94%.…”
Section: Resultsmentioning
confidence: 99%